Pemenuhan Hak-hak Warga Binaan Hamil di Lembaga Pemasyarakatan Perempuan Kelas II A Bandar Lampung - Diajeng Dwi Andini; Intan Pelangi (JURIDISCH DENKEN, 2025)
The discussion in this paper is entitled Fulfillment of the Rights of Pregnant Prisoners in Class IIA Women's Correctional Institution Bandar Lampung which is a study to find out how the guidance provided by the Class IIA Women's Correctional Institution Bandar Lampung to pregnant women inmates. Because basically female inmates have different natures from men, such as menstruation, pregnancy, childbirth, and breastfeeding. The formulation of the problem in this study consists of the first to examine how to fulfill the rights of inmates who are pregnant in Class IIA Women's Correctional Institution Bandar Lampung and are there any inhibiting factors in fulfilling the right to obtain health services for inmates who are pregnant? This type of research is a field using an empirical juridical approach. The empirical juridical approach is the collection and discovery of data and information through field studies at the Class IIA Women's Correctional Institution in Bandar Lampung, aiming to study the reality that occurs in the field. This study concluded that the fulfillment of the rights of the inmates who were pregnant and breastfeeding had been fulfilled properly in accordance with Law Number 12 of 1995.